EVALUATION OF ELITE JU-JITSU ATHLETES’ PHYSICAL FITNESS USING THE JMG TEST - ZAGGELIDIS, Georgios; ZAGGELIDIS, Christos; MALKOGEORGOS, Alexandros (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2019)
The JMG test has been widely used since 1982 and has been included in performance testing in many national federations, especially judo’s. The study was conducted using the JMG (Jose Manual Garcia) test, to evaluate the physical fitness of ju-jitsu international federation’s elite ju-jitsu athletes, during a five days training camp (precompetitive period). The athlete performs three exercises for 1 minute each (a total of 3 minutes) and the goal is to measure ju-jitsu’s functional capacities. Eighteen (No=18) athletes, aged from 16 to 22 years, 12 males and 6 females, were tested. Their fitness was assessed, according to the test, from poor to excellent. The test’s results show that JMG test can be used by athletes of Fighting System (ju-jitsu international federation) which is articulated in a three-minute combat.